Farm business management : the human factor - Nuthall, P. L. [ (Peter Leslie)] (CAB International, 2010)
Explores the role of the psychology of the manager running the farm business, the person responsible for staff, strategic decisions and financial success or failure. This book addresses fundamental questions such as the process of decision making, persoal skills, and methods to improve managerial ability.